Seed-Borne Fungi Associated with Diverse Rice Varieties Cultivated in the Western North Region of Ghana - Ackaah, Francis Mensah; Nyaku, Seloame Tatu; Darkwa, Edmund (International Journal of Microbiology, 2023)
Rice is a major staple in the Ghanaian diet. However, its production is constrained by fungal diseases. A survey was conducted in 2018 in three selected districts in the Western North Region of Ghana using a structured questionnaire and face-to-face interaction with 230 farmers to assess their knowledge, perceptions of seed-borne fungal diseases, and management practices. Additionally, fungi associated with farmer’s seeds were isolated and identified through the Agar and Blotter tests. Findings indicate that 72.7% of the farmers in the selected districts relied on their saved seeds for planting. Thirteen fungal genera were associated with the rice seed samples collected from the three districts. The Juaboso district had the majority (13) of seed-borne fungi. The seed samples were categorized into various forms of discolouration, and significant differences (P<0.05) existed among the seed samples for this parameter. The AGRA rice, a farmer-saved seed from Juaboso, had the highest level of seed discolouration (41.96%). Fungi identified to be associated with the dark brown/brown discolouration of rice seeds were Bipolaris spp., Fusarium spp., Macrophomina phaseolina and Aspergillus spp. The only fungus associated with the yellow/pale yellow colour was Bipolaris spp. The fungi Bipolaris spp., Curvularia spp., and Botryodiplodia spp. were associated with the dark spot discolouration. Alternaria spp., and Aspergillus spp. were observed on the greyish white seed discolouration sample. Fungi are associated with rice cultivation and vary according to district and rice variety. A complex of pathogenic and saprophytic fungi therefore infects rice grains both in field and storage conditions.